Anticipating Indonesia’s Lithium Mining and Electric Vehicle Industry: Legal and Policy Insights from Australia’s Regulatory Framework - Oliviere, Shawn; Valencia, Jeralyn (Law Review, 2024)
The international shift toward lithium-based battery technologies poses significant challenges to Indonesia’s long-term competitiveness. Drawing on the country’s experience with environmental degradation in nickel mining, this study underscores the need for Indonesia to strengthen its legal and institutional frameworks to sustainably govern future lithium extraction. This research analyzes Indonesia’s strategic positioning in the global electric vehicle (EV) industry, primarily driven by its abundant nickel reserves. A comparative legal analysis is conducted against Australia’s regulatory regime, which features strong enforcement, environmental safeguards, and post-mining rehabilitation obligations. While structural global asymmetries may limit Indonesia’s capacity to pursue ideal reforms, the country must proactively enhance its domestic governance mechanisms. This research employs a normative juridical approach, relying on statutes, policy documents, and academic commentary. The findings highlight gaps in licensing enforcement, public participation rights, and mine closure governance. Based on Australia’s best practices, this article proposes targeted policy reforms that aim to improve Indonesia’s legal capacity to govern its critical mineral resources sustainably and equitably in the EV era.